2014
DOI: 10.2319/032414-221.1
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of shear bond strength of brackets recycled using micro sandblasting and industrial methods

Abstract: Objective: To evaluate in vitro the shear bond strength of brackets recycled by sandblasting with aluminum oxide particles of different sizes or reconditioned industrially after successive rebonding. Materials and Methods: Eighty brackets were bonded and debonded sequentially three times. After the first debonding, brackets were divided into four groups: (group 1) sandblasting with aluminum oxide particles of 25 m, (group 2) 50 m, and (group 3) 110 m, and (group 4) industrial recycling. Bond strength and adhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 23 publications
0
24
0
1
Order By: Relevance
“…In addition, an increase in bond strength in the third recycling in the sandblast group might be due to an increase in the porosity of the base of the brackets caused by sandblasting used in the present study which is in line with the results of other studies. 1 , 23 In laser groups, a decreasing pattern in SBS from new brackets to 3 times of recycling was noted. Differences in SBS in pre-recycling (new brackets) group and other laser subgroups were significant.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…In addition, an increase in bond strength in the third recycling in the sandblast group might be due to an increase in the porosity of the base of the brackets caused by sandblasting used in the present study which is in line with the results of other studies. 1 , 23 In laser groups, a decreasing pattern in SBS from new brackets to 3 times of recycling was noted. Differences in SBS in pre-recycling (new brackets) group and other laser subgroups were significant.…”
Section: Discussionmentioning
confidence: 88%
“…Employing previous data with a desired power of 90% at a significance level of 5%, 23 - 25 a sample size of 11 pairs was needed to detect a difference of 2.53 between the two means, which was increased to 15 pairs in order to allow for probable losses.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have reported that recycling with aming results in shear bond strength below the recommended range of clinical need (4,5,7,8), while recycling with sandblasting gives clinically acceptable shear bond strength. (4,(8)(9)(10)(11)(12)(13)) SBS of brackets recycled by aming with sandblasting was reported much less in a study by Gupta et al (2.05 MPa) (10) and large value (26.94 MPa) was reported in a study by Bansal et al (11) . However, limited studies are available in literature about the effects of recycling orthodontic brackets with ultrasonic cleaning on shear bond strength.…”
Section: Introductionmentioning
confidence: 99%
“…Different methods have been proposed to remove the remaining adhesive from the ceramic bracket base for rebonding [11] . Inoffice methods such as heating methods (direct heating), mechanical methods (sandblasting or using green stone or tungsten carbide bur) [12,13,14] , and recently laser have been used for bracket recycling. Demand for use of laser in orthodontic had increased during the past years [15] .…”
Section: Introductionmentioning
confidence: 99%